ANALYSIS OF TRIGGERING FACTORS OF VIOLENCE IN CHILDREN GENDER-BASED IN BENGKALIS REGENCY - Roha, Muf; Saifunnajar, Saifunnajar; Sumarni, Titin (Marwah: Jurnal Perempuan, Agama dan Jender, 2024)
This study aims to find out how  the forms of gender-based child violence occur in Bengkalis Regency and what are the triggering factors for gender-based child violence in Bengkalis Regency. The method in this study is qualitative descriptive, data collection is carried out through direct interviews with counselors and heads of fields and heads of UPT as well as counselors and psychologists at related institutions, and documentation, namely taking and requesting data on cases of violence that have been handled by UP2 and LK3 in Bengkalis Regency. After data collection and interviews and analysis, it can be concluded that: 1) Forms of gender-based child violence in Bengkalis Regency include sexual intercourse with children, molestation of children, sexual abuse of children, rape of children, domestic violence against children, fights between children, abuse of children, beating of children, neglect or disposal of babies, abuse of children, exploitation of children,  morality, bullying against children, children's rights, threats against children, trafficking against children, sodomy against children, illegal logging against children. 2) Factors that trigger gender-based violence against children in Bengkalis Regency include there are still some people who weaken other genders, parenting and family factors, environmental factors, peers, social media or gadgets.